Inverse heat transfer problems: an application to bioheat transfer - Rojczyk, Marek; Orlande, Helcio R. B.; Colaço, Marcelo J.; Szczygieł, Ireneusz; Nowak, Andrzej J.; Białecki, Ryszard A.; Ostrowski, Ziemowit (Computer Assisted Methods in Engineering and Science, 2017)
In this work, we applied the Markov chain Monte Carlo (MCMC) method for the estimation of parameters appearing in the Pennes' formulation of the bioheat transfer equation. The inverse problem of parameter estimation was solved with the simulated transient temperature measurements. A one-dimensional (1D) test case was used to explore the capabilities of using the MCMC method in bioheat transfer problems, specifically for the detection of skin tumors by using surface temperature measurements. The analysis of the sensitivity coefficients was performed in order to examine linear dependence and low sensitivity of the model parameters. The solution of the direct problem was verified with a commercial code. The results obtained in this work show the ability of using inverse heat transfer analysis for the detection of skin tumors.